Enhanced π–π Interactions of Nonfullerene Acceptors by Volatilizable Solid Additives in Efficient Polymer Solar Cells. Issue 18 (25th March 2019) - Yu, Runnan; Yao, Huifeng; Chen, Zhenyu; Xin, Jingmin; Hong, Ling; Xu, Ye; Zu, Yunfei; Ma, Wei; Hou, Jianhui
Abstract: Fine‐tuning of the nanoscale morphologies of the active layers in polymer solar cells (PSCs) through various techniques plays a vital role in improving the photovoltaic performance. However, for emerging nonfullerene (NF) PSCs, the morphology optimization of the active‐layer films empirically follows the methods originally developed in fullerene‐based blends and lacks systematic studies. In this work, two solid additives with different volatilities, SA‐4 and SA‐7, are applied to investigate their influence on the morphologies and photovoltaic performances of NF‐PSCs. Although both solid additives effectively promote the molecular packing of the NF acceptors, due to the higher volatility of SA‐4, the devices processed with SA‐4 exhibit a power conversion efficiency of 13.5%, higher than that of the control devices, and the devices processed with SA‐7 exhibit poor performances. Through a series of detailed morphological analyses, it is found that the volatilization of SA‐4 after thermal annealing is beneficial for the self‐assembly packing of acceptors, while the residuals due to the incomplete volatilization of SA‐7 have a negative effect on the film morphology. The results delineate the feasibility of applying volatilizable solid additives and provide deeper insights into the working mechanism, establishing guidelines for further material design of solid additives. Abstract : Two solid additives are proven to improve the molecular packing of acceptors, while devices processed with different additives exhibit different photovoltaic performances due to the different volatilities. The working mechanism and basic design rules of solid additives are revealed, and a feasible method for achieving high‐efficiency polymer solar cells is established.